2019
DOI: 10.1007/s11229-019-02140-w
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of uncertainty in ecological rationality

Abstract: Despite the ubiquity of uncertainty, scientific attention has focused primarily on probabilistic approaches, which predominantly rely on the assumption that uncertainty can be measured and expressed numerically. At the same time, the increasing amount of research from a range of areas including psychology, economics, and sociology testify that in the real world, people's understanding of risky and uncertain situations cannot be satisfactorily explained in probabilistic and decision-theoretical terms. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 93 publications
0
72
0
Order By: Relevance
“…2 Ecological rationality places the decisionmaker back into their ecological context. Broadly defined, ecological rationality can be understood in terms of cognitive success in the world, or the fit between the mind and the environment (Kozyreva and Hertwig 2019;Gigerenzer and Todd 1999;Todd and Brighton 2016). Thus, an action is ecologically rational if it is cognitively successful given a certain environmental context.…”
Section: Ecological Rationalitymentioning
confidence: 99%
See 3 more Smart Citations
“…2 Ecological rationality places the decisionmaker back into their ecological context. Broadly defined, ecological rationality can be understood in terms of cognitive success in the world, or the fit between the mind and the environment (Kozyreva and Hertwig 2019;Gigerenzer and Todd 1999;Todd and Brighton 2016). Thus, an action is ecologically rational if it is cognitively successful given a certain environmental context.…”
Section: Ecological Rationalitymentioning
confidence: 99%
“…Thus, ecological rationality deals with how the minds of organisms compensate for their bounded cognitive resources by exploiting the structures and regularities of information in the task environments in which they are applied. From an ecological point of view, rational behaviour can therefore be understood as the adaptive capacity of an organism to achieve its intentions "under the constraints and affordances posed by both the environment and its own cognitive limitations" (Kozyreva and Hertwig 2019).…”
Section: Ecological Rationalitymentioning
confidence: 99%
See 2 more Smart Citations
“…In bounded situations such as when people have limited time or lack useful information, they often solve problems well by using heuristics (e.g., Herzog & Hertwig, 2013;Marewski & Schooler, 2011;Otworowska, Blokpoel, Sweers, Wareham, & van Rooij, 2018), meaning that they make ecologically rational inferences through the use of simple strategies. Herbert Simon proposed the metaphor that effective behaviors are generated when context (environmental structures) and cognition (human computational capabilities) fit together like the blades of a pair of scissors-one blade being environmental structures and the other being human cognitive capacity (i.e., "Simon's scissors" metaphor) (Simon, 1990; see also Kozyreva & Hertwig, 2019;Lockton, 2012;Todd & Brighton, 2016). In fact, many previous works have demonstrated that, using binary choice tasks, the effectiveness of people's subjective memory experiences as inference cues is clearly explained in terms of the real-world environmental structures (e.g., Goldstein & Gigerenzer, 2002;Hertwig, Herzog, Schooler & Reimer, 2008;Herzog & Hertwig, 2013;Honda, Abe, Matsuka & Yamagishi, 2011;Honda, Matsuka & Ueda, 2017;Schooler & Hertwig, 2005;Xu, Gonz alez-Vallejo, Weinhardt, Chimeli & Karadogan, 2018; as a review, see Gigerenzer & Goldstein, 2011).…”
Section: Ecological Rationality and Simon's Scissorsmentioning
confidence: 99%